Giant Pressure‐Driven Lattice Collapse Coupled with Intermetallic Bonding and Spin‐State Transition in Manganese Chalcogenides. Issue 35 (27th July 2016) - Wang, Yonggang; Bai, Ligang; Wen, Ting; Yang, Liuxiang; Gou, Huiyang; Xiao, Yuming; Chow, Paul; Pravica, Michael; Yang, Wenge; Zhao, Yusheng
Abstract: Materials with an abrupt volume collapse of more than 20 % during a pressure‐induced phase transition are rarely reported. In such an intriguing phenomenon, the lattice may be coupled with dramatic changes of orbital and/or the spin‐state of the transition metal. A combined in situ crystallography and electron spin‐state study to probe the mechanism of the pressure‐driven lattice collapse in MnS and MnSe is presented. Both materials exhibit a rocksalt‐to‐MnP phase transition under compression with ca. 22 % unit‐cell volume changes, which was found to be coupled with the Mn 2+ (d 5 ) spin‐state transition from S =5/2 to S =1/2 and the formation of Mn−Mn intermetallic bonds as supported by the metallic transport behavior of their high‐pressure phases. Our results reveal the mutual relationship between pressure‐driven lattice collapse and the orbital/spin‐state of Mn 2+ in manganese chalcogenides and also provide deeper insights toward the exploration of new metastable phases with exceptional functionalities. Abstract : Under pressure : Giant lattice collapses during the pressure‐driven phase transition in manganese chalcogenides are associated with the formation of intermetallic bonds and high‐to‐low spin state transition.